Advokasi Transnasional Malala Fund dalam Merespon Krisis Pendidikan Perempuan di Afghanistan Pasca Kembalinya Taliban (2021-2025) - Hesti Rosdiana; R. Maisa Yudono; Lia Wulandari; Hartika Arbiyanti (Institut Nalanda, 2026)
Since the Taliban seized power in Afghanistan in August 2021, the country has become the world’s most extreme case gender-based educational exclusion. This article analyzes the transnational advpcay strategies employed by the Malala Fund in response to the crisis of female education in Afghanistan. Utilizing a qualitative case study approach, this research operationalizes the Transnational Advocacy Networks (TANs) framework and the concept of Norm Entrepreneurship by Keck&Sikkink (1998) as its primary analytical lenses. The findings indicate that the Malala Fund functions simultaneously as a network hub and a norm entrepreneur through four strategic dimensions: deploying emergency grants to support the evacuation and resettlement of human rights defenders, building documentation infrastructure in partnership with local and international organizations, forging cross-sectoral coalitions to expand access to free secondary education, and executing normative reframing through the strategic codification of the term “gender apartheid” as both a legal instrument and a symbolic mobilization tool. However, the effectiveness of this advocacy is significantly constrained by the Taliban’s systematic closure of domestic advocacy channels, the absence of enforceable international legal mechanism, and geopolitical fragmentation within the UN Sceurity Council. This contribute to the literature by demonstrating how non state actors utilize norm entrepreneurship to elevate domestic gender crises into the global normative agenda, while highlighting the structural limits of transnational advocacy when state sovereignty claims are weaponized to dismiss international human rights norms.